2016
DOI: 10.18632/oncotarget.8115
|View full text |Cite
|
Sign up to set email alerts
|

Armored long non-coding RNA MEG3 targeting EGFR based on recombinant MS2 bacteriophage virus-like particles against hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is one of the most frequently diagnosed cancers worldwide. However, the treatment of patients with HCC is particularly challenging. Long non-coding RNA maternally expressed gene 3 (MEG3) has been identified as a potential suppressor of several types of tumors, but the delivery of long RNA remains problematic, limiting its applications. In the present study, we designed a novel delivery system based on MS2 virus-like particles (VLPs) crosslinked with GE11 polypeptide. This vector … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
89
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 83 publications
(89 citation statements)
references
References 58 publications
(65 reference statements)
0
89
0
Order By: Relevance
“…Previously, MEG3 was incorporated into HCC cells by using a new delivery system, which suppressed tumor growth through p53. This finding showed that MEG3 may have tumor suppressive function in HCC . Also, MEG3 was identified to be a molecular sponge for miR‐664 inhibiting cell proliferation via miR‐664‐dependent ADH4 regulation .…”
Section: Long Noncoding Rnas Signaling In Hccmentioning
confidence: 81%
See 4 more Smart Citations
“…Previously, MEG3 was incorporated into HCC cells by using a new delivery system, which suppressed tumor growth through p53. This finding showed that MEG3 may have tumor suppressive function in HCC . Also, MEG3 was identified to be a molecular sponge for miR‐664 inhibiting cell proliferation via miR‐664‐dependent ADH4 regulation .…”
Section: Long Noncoding Rnas Signaling In Hccmentioning
confidence: 81%
“…The expression of lncRNAs can be manipulated by specific siRNAs or antisense oligonucleotides or exogenous overexpression . Previously, a study demonstrated that introduction of tumor suppressor MEG3 into HCC tumor via a novel delivery system promoted apoptosis, an effect that confirms the pharmacological value of lncRNA‐based therapy as an option with few adverse effects. Hence, we anticipate that further advanced studies exploiting modern research tools will expose deeper mechanisms of lncRNA action and add to the development of lncRNA‐based diagnostic and therapeutic agents for HCC management.…”
Section: Long Noncoding Rnas Signaling In Hccmentioning
confidence: 95%
See 3 more Smart Citations